Ictal headache: Insights from two cases. (November 2018) - Taga, Arens; Florindo, Irene
Background: We report the first literature description of ictal epileptic headaches closely mimicking glossopharyngeal neuralgia and short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing. Case 1: A 37-year-old man complained of short-lasting, electric-shock like headache, confined to the pharynx. During the episodes, he could not speak because he felt "words blocked at the throat". An EEG recorded epileptic discharges concomitant with headache; a brain MRI disclosed frontal polymicrogyria. Case 2: A 66-year-old man complained of short-lasting, right periocular headache, associated with ipsilateral ptosis, conjunctival injection and lacrimation. Some episodes were followed by tonic contraction of the right facial and limb muscles; on one occasion, headache was followed by a generalized seizure. A brain MRI revealed hippocampal abnormalities. Discussion: These cases highlight the complex relationship between headache and epilepsy, and suggest a possible contribution of cortical structures to the genesis of paroxysmal headaches such as glossopharyngeal neuralgia and short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing.